Violation of the right to defence in the administrative procedure for the inspection of fishing activities - Torres Vega , Romelia María (2025)
During the inspection procedures associated with fishing activities, it is necessary to ensure the right to defence of the holders of such authorisations, preventing their guarantees from being violated. By virtue of this, the objective of this article is to analyze the violation of the right to defense in the framework of fisheries inspections in Ecuador, based on the regulations of the Organic Law of Fisheries and Aquaculture (LOPAD) and its regulations. The inspection procedure was described, highlighting the mechanisms that guarantee the supervision and control of fishing activities so that the fishing inspections carried out by the public administration do not violate the right to defense of fishermen and fishing vessels. The methodology was qualitative; using the documentary and descriptive research method, information was collected through laws, books and other sources of information. The results show the absence of procedural guarantees for those inspected, which allow refuting the information collected and preliminary findings in the previous action of fishing inspections violates the right to defense. Based on these findings, a reform of Article 219 of the regulations of the Organic Law on Fisheries and Aquaculture was proposed.